Nilai-Nilai Etika dalam Praktik Jual Beli Perspektif Fikih Muamalah - Devi Agustina; Fannia Masrur Aini (Program Studi Hukum Ekonomi Syariah STAI As-Sunnah Deli Serdang, Sumatera Utara, 2025)
Buying and selling is a means of exchange between sellers and buyers to meet each other's needs, but it requires ethics in its execution to ensure good communication. The main objective of this research is to analyze the ethical principles in buying and selling transactions according to the Islamic perspective, based on sources of jurisprudence and classical as well as contemporary literature. This research is qualitative research using a library research approach. Library research was conducted by tracing, examining, and analyzing literature relevant to the research topic, including books, journal articles, dissertations, and other credible sources. The results of this study indicate that business ethics from an Islamic perspective encompass five main principles: (1) honesty and trustworthiness in transactions, (2) prohibition of usury, (3) obligation to sell halal goods, (4) emphasis on the quality of goods sold, and (5) importance of clear contracts agreed upon by both parties. These principles aim to achieve justice and blessings in transactions.